Oxidative stress in dogs during mid-gestation abortion: Fetal and maternal antioxidant alterations with clinical and hematological features - Özalp, Gozde; Gül, Z; Seyidoglu, N; Büyükuysal, L (Journal of the Hellenic Veterinary Medical Society, 2022)
The present study aimed to evaluate the GSH and MDA levels in dog’s serum and vital organs of aborted fetuses, after application of two abortifacient. Animals of group I (n = 6) were treated twice with subcutaneous injection of 10 mg/kg aglepristone and group II (n = 3) received prostaglandin F2α at a dose of 125 μg/kg every 12 hours until abortion process completed. Hematologic examinations and sedimentation rates were performed of bitches. The duration between first occurrence of vaginal discharge to first expulsion of fetuses ranged between 14-29 hours (mean: 22.6±5.5 h) and 24-33 hours in group I and II, respectively. Both treatments significantly increased the serum MDA levels (P<0.01); however aglepristone increased the MDA levels throughout the study, prostaglandin enhanced plasma MDA levels only on day 1. GSH levels were significantly lower in aglepristone-treated bitches than prostaglandin-treated animals (P<0.05). The treatments resulted similar MDA levels in liver and heart tissues (P>0.05). GSH levels in kidney, muscle and heart tissues did not differ between groups (P>0.05), aglepristone resulted reduced GSH levels in liver tissue (P<0.05). High MDA levels could be evaluated as a useful marker for fetal suffering in pregnancy controls. The MDA and GSH levels, measured in vital organs of fetuses, could suggest possible toxic effects of abortifacients in newborns, as both medical agents are being used in parturition induction.